Accuracy of clinical diagnosis of benign eyelid lesions: Is a dedicated nurse-led service safe and effective?. (3rd July 2016) - Mohite, Abhijit A.; Johnson, Andria; Rathore, Deepa S.; Bhandari, Kamal; Crossman, Richard; Mehta, Purnima; Ahluwalia, Harpreet S.
ABSTRACT: This article compares an independent nurse-led benign lesion service with a doctor-led one, and assesses the impact of clinician seniority on diagnostic accuracy rates. Retrospective review of benign lesions referred to a teaching hospital and managed in either a doctor- or nurse-led lid service. All lesions were diagnosed clinically, excised and then sent for histological diagnosis. Lesions were categorized into subtypes. Pre-excision clinical diagnoses were compared with histological diagnoses. Sensitivity, specificity and missed malignancy rates were calculated for each subtype. Accuracy was compared between different grades of doctors and a specialist nurse. 264 and 332 lesions were managed in a doctor-led and nurse-led service, respectively. Rates of accurate sub-typing were 79.6% and 80.4% in the doctor- and nurse-led services, respectively (p > 0.05). Clinician seniority had no bearing. Missed malignancies or pre-malignancies accounted for 1.1% and 1.5% of lesions in the doctor and nurse-led services, respectively (p > 0.05). Overall, the remaining misdiagnoses were benign lesions of another subtype (13.6%) or non-specific histological findings (5.0%) and 98.6% of lesions were confirmed as benign on histology. Overall sensitivity and specificity values were: benign epithelial proliferations 95.6% and 92.2%, epidermal inclusion cysts 92.2% and 88.0%, xanthelasma 97.5% and 100.0%, cysts of Moll 66.7% and 96.6%, naevi 39.4% and 99.8% and molluscum 20.0% and 99.8%, respectively. A dedicated nurse-led service is as effective in managing a range of clinically benign lid lesions as a doctor-led one, and clinician seniority has little impact on the diagnostic accuracy of these lesions.